Effect of polymer structure on the molecular dynamics and thermal behavior of poly(allyl acetoacetate) and copolymers - Grzybowska, Katarzyna (2014)
In this paper, dielectric and calorimetric studies of the small-molecule glass former allyl acetoacetate monomers as well as its newly synthetized homopolymer and copolymers with different styrene composition were performed in both the liquid and glassy states. The molecular dynamics studies by the broadband dielectric spectroscopy and the stochastic temperature modulated differential scanning calorimetry enabled us to explore relaxation processes of examined materials in the wide frequency range. We found that the copolymers reveal two co-existing glass transitions characterized by the glass transition temperatures, which are very close to those of the corresponding homopolymers. These results suggest that the copolymers exhibited some sequences of acetoacetate units with a microphase-separated morphology in agreement with the value of reactivity ratio previously determined. We investigated effects of copolymerization compositions on the glass transition temperature, the isobaric fragility index, the dielectric and calorimetric intensity, and the dynamic heterogeneity on the glass transitions of the materials.